Alternative splicing of a Drosophila tropomyosin gene generates muscle tropomyosin isoforms with different carboxy-terminal ends. - Basi, G S (1984)
The muscle tropomyosin I (mTm I) gene from Drosophila melanogaster has been analyzed and shown to express a complex transcription unit consisting of two sets of tissue-specific mRNAs. A 1.3- and 1.6-kilobase set of mRNAs is expressed during myogenesis in embryos, and in myogenic cell cultures. The mRNAs encode a 34,000-dalton muscle tropomyosin isoform. The same mTm I gene expresses a different set of 1.7- and 1.9-kilobase mRNAs in thoracic flight muscle tissue of the adult. The thorax RNAs encode a new tropomyosin isoform resolved on two-dimensional gels. The structure of the gene has been determined, and we show that the embryonic and thoracic mRNAs are generated by alternative splicing. The alternate exon splicing patterns determine a different 27 amino acids at the carboxy-terminal end of the two tropomyosin isoforms. These results show that the carboxy-terminal domain of tropomyosin is highly regulated in determining tropomyosin function. The results also show that contractile protein isoforms can be generated by single as well as multiple genes.